A ANALYSIS OF PATIENT CHARACTERISTICS ASSOCIATED WITH QUALITY OF LIFE OF HEART FAILURE PATIENTS AT ULIN REGIONAL GENERAL HOSPITAL IN BANJARMASIN - Hanura Aprilia (Journal of Nursing Invention)
Background: Heart Failure disease causes a decline in physical and psychological function, failure to implement the principles of care for heart failure patients can result in decreased quality of life, wasteful hospitalization and faster death. Objective: To determine the characteristics of respondents associated with the quality of life of patients with heart failure disease. Methods: This study uses correlation analytics with a cross sectional design. The number of samples in this study were 100 respondents. Results: In the results of this study that the characteristics of respondents who affect the quality of life of heart failure patients are physical function with a p-value of 0.000 ≤ α with OR: 10.578 (4.124-27.133) Conclusion: There is a relationship between physical function and the quality of life of heart failure patients at the Heart Polyclinic of Ulin Banjarmasin Regional General Hospital with p value = 0.000.